ANALISIS STRATEGIS BERBASIS SWOT TERHADAP ADOPSI ENERGI TERBARUKAN PADA INDUSTRI MANUFAKTUR: IMPLIKASI TERHADAP KEBERLANJUTAN DAN EFISIENSI OPERASIONAL - Rahman Soesilo (LENVARI, 2026)
This study evaluates renewable energy adoption in an Indonesian manufacturing firm using a SWOT framework (Strengths, Weaknesses, Opportunities, Threats) to inform sustainability and operational efficiency strategies. A qualitative case study in February–March 2026 used semi-structured interviews, internal records on energy use and projects, and limited observation of the utility system. Factors were coded and prioritized with weighted internal and external factor summaries (IFAS and EFAS), then converted into options through a TOWS strategy matrix. Results show moderate internal readiness (IFAS 2.57) driven by managerial commitment, ongoing energy-saving routines, available utility data, and continuous improvement, but limited by upfront investment pressure, weak energy analytics, dependence on external maintenance, and coordination gaps. The external context is also moderate (EFAS 2.47): low-carbon supply-chain expectations and supportive programs offer opportunities, while policy uncertainty and techno-economic risks remain threats. The study concludes that renewable energy initiatives should be embedded in energy governance, supported by transparent investment business cases and capability development, and implemented in phases from pilot to scale. Firms should maintain an energy roadmap and monitor energy intensity and emissions to sustain measurable cost and reputation gains. Integrating energy indicators into operational targets helps align production reliability, cost control, and decarbonization objectives across functions.